Benefits of individual imaging methods for diagnosis and monitoring of activity of multiple myeloma - Vanicek, J; Szturz, P; Rehak, Z; Kianicka, B; Bulik, M (Klinicka onkologie, 2012)
BACKGROUND: Multiple myeloma pathogenesis, pathology, symptoms and imaging techniques used in clinical diagnostic algorithm, the indications and the differences between currently available imaging methods. DESIGN: The article describes advantages and disadvantages of basic X-ray imaging and recommended skeleton screening, as the method of first choice, followed by description of the most frequently affected areas and Mirels score. The present golden standard magnetic resonance (MR) imaging, its potential and also recommended MR indications. Concerning computer tomography (CT) imaging, mainly comparison between CT and MR and X-ray imaging its indications and benefits as the interventional instrument are mentioned. The arcticle also focuses on the role of skeleton scintigraphy with Tc-pyrophosphate, which is not recommended today, and the role of positron emission tomography with fluorodeoxyglucose (FDG-PET) in the assessment of the therapy effectiveness and prognosis for patients, its future and present limitations. The next commonly used radioisotope imaging with 99Tc-sestamibi (MIBI) and its comparison to other methods, especially to the FDG-PET and recommended indications for both techniques. Last aim is description of specification of bone tissue density with Dual Energy X-ray Absorption scanning method (DEXA). CONCLUSION: These imaging methods are commonly used as additional diagnostic tests in initial diagnostic -work-up and in follow-up due to frequent relapses of multiple myeloma.
Keywords: magnetická rezonanční tomografie; Magnetic Resonance Imaging; mnohočetný myelom; Humans; Multiple Myeloma; počítačová rentgenová tomografie; pozitronová emisní tomografie; Positron-Emission Tomography; Tomography, X-Ray Computed; lidé